The Influence of Leader Humor on Job Satisfaction with LMX As A Mediator Variable - Delly Mursanty; Muhammad Rasyid Abdillah; Ali Asfar (SAINS ORGANISASI, 2023)
The purpose of this study was to determine the effect of leader humor on job satisfaction and leader-member exchange at the Rokan Hilir Regency Regional Disaster Management Agency and to determine the effect of Leader humor on job satisfaction through Leader-member exchange at the Rokan Hilir Regional Disaster Management Agency. The population in this study were all employees at the Rokan Hilir Regency Regional Disaster Management Agency, which, based on observations, totaled 77 people. The sample that makes up is the entire population or saturated sample. Thus the sample in this study amounted to 77 employees. Based on the results of the analysis, it can be concluded, 1) The first hypothesis is that Leader-member exchange has a positive effect on job satisfaction. The results of the hypothesis test showed a t value of 11.289 with a sig. 0.000 then H1 is accepted. 2) The second hypothesis is that Leader humor has a positive effect on job satisfaction. The results of the hypothesis test showed a t value of 3.340 with a sig. 0.001 then H2 is accepted. 3) The third hypothesis is that Leader humor has a positive effect on leader-member exchange. The results of the hypothesis test showed a t value of 5.894 with a sig. 0.000 then H3 is accepted. 4) The fourth hypothesis is that Leader humor influences job satisfaction with LMX as a mediator variable. The results of the hypothesis test showed a t value of 6.004 with a sig. 0.000 then H4 is accepted